Photodegradation of benzene and phenanthrene in aqueous solution using pulsed ultraviolet light - Lee, Hanuk; Yoon, Yeomin; Her, Namguk; Han, Jonghun; Oh, Jeill; Park, Jae-Woo (KSCE journal of civil engineering, 2017)
This study examined the comparative degradation of benzene and phenanthrene using a pulsed ultraviolet light (PUV) reactor. The concentration of free chlorine was determined for various NaCl concentrations (0-10 mM) and electrode distances (10, 20, and 40 cm) in order to investigate the effect of oxidation by free chlorine on degradation. It was observed that the presence of NaCl had a dual effect on benzene removal, while phenanthrene removal increased with decreasing NaCl concentration. Both benzene (0.065 min −1 ) and phenanthrene (0.24 min −1 ) pseudo first-order rate constants were highest with a NaCl concentration of 0.25 mM and an electrode distance of 10 cm. The degradation of phenanthrene was much higher than that of benzene due mainly to smaller Dewar’s reactivity values ranging from 1.80 to 2.18 at five different positions for phenanthrene compared to the one position of benzene (2.31), which suggests that phenanthrene is more easily attacked than benzene.